(untitled) (Mūzikas akadēmijas raksti, 2024)
Concept is a new term applied to the Latvian music of the early 21st century. The idea of concept is borrowed from visual arts. It refers to the conceptual art that emerged in the late 1960s in the USA and in Europe. It focuses on verbal ideas and treats an artwork as a medium for transmission of these ideas. The conceptual art suggests a new form of art perception: these artworks should be regarded not only as visual ones, but mostly as ideas that can be expressed linguistically. Likewise, some of the new Latvian composers, Andris Dzenītis, Mārtiņš Viļums, Santa Bušs, etc., suggest that verbally explicated ideas are crucial in some of their instrumental works. It is recommended to the listener to learn about its content in linguistic terms. Although the idea is expressed musically, it might not be perceived adequately if the listener ignores the concept stated by the author in words. The main link of conceptual art with the concept music would be a meaning that demands a verbal explanation. The term concept can be transmitted from the theory of art to music without changing its main theoretical aspects. Borrowing of the term would mean that there is a shift of media from visual to acoustic without essential changes of the term itself as it is formed in a wide range of art theory sources. The large supply of texts dedicated to the conceptual art and its developed definitions would serve as a firm basis for this research.